Influence of the storage conditions of sucupira´s seeds alcoolatures (Pterodon emarginatus) in the presence of their bioactive metabolites (Research, Society and Development, 2020)
The treatment of inflammatory conditions using herbal medicines prepared by macerating sucupira seeds in alcoholic beverages is a common practice. The volatility and lability of the metabolites can promote variations in the chemical composition of herbal medicines, according to the storage conditions. This work aimed to investigate how storage affects the chemical profile of hydroalcoholic extracts of sucupira seeds, mainly in relation to the presence and relative concentration of bioactive metabolites. For this purpose, macerations of sucupira seeds 10% (w/v) in alcohol 70 ° GL and in duplicate were prepared. The packaging of these was carried out in transparent and amber bottles that were stored in different conditions: in direct contact with solar radiation, at room temperature, in a refrigerator and freezer. After 15, 45, 90 and 155 days, aliquots were removed from each sample and these had their chemical profiles determined by gas chromatography technique coupled to mass spectrometry (CG-EM). The storage for periods of 15, 45 and 90 days led to a significant chemical change, only of the samples exposed simultaneously to heat and sunlight. At 115 days of storage, the samples stored in an amber flask, in the other storage conditions, did not exhibit all the extracted metabolites, but maintained the presence of compounds that have anti-inflammatory action. For these results it is possible to conclude that the homemade preparations, stored at room temperature, under refrigeration and frozen, will maintain the presence of the metabolites of anti-inflammatory action even when stored for 115 days, regardless if this storage occurs in an amber or transparent bottle.